Faktor yang Mempengaruhi Tax Avoidance pada Perusahaan Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2019–2021 - St. Khofifah; Mira Pramudianti (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to analyze the factors that influence tax avoidance in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. The independent variables analyzed in this study include profitability, sales growth, and leverage. This study uses secondary data in the form of annual financial reports of companies obtained from the official website of the Indonesia Stock Exchange. The method used in this study is multiple linear regression analysis with samples selected through purposive sampling method. This study examines the effect of each independent variable on tax avoidance, which is measured using the Effective Tax Rate (ETR) proxy. The results of the study indicate that profitability has a significant effect on tax avoidance, where companies with higher levels of profitability tend to avoid taxes. Meanwhile, sales growth has a significant effect on tax avoidance. Leverage also shows a positive effect on tax avoidance, indicating that companies with high debt levels tend to use interest expenses to reduce their tax liabilities. This study provides implications for regulators and policy makers to strengthen supervision of tax avoidance practices, especially in companies that have certain characteristics such as high profitability sales growth and leverage.